The Role of Uterine Infection in Pregnancy Outcome: A Case Report - Tatyana Bodurska; Emiliana Konova; Svetlana Pachkova; Angel Yordabnov (Journal of Biomedical & Clinical Research)
It was believed in the past that only the lower genital tract is inhabited by microorganisms, and the cervix was considered as a perfect barrier against the ascension of microbes. Nowadays, many studies using new sequencing technologies examining microbiomes with low biomass show that the microorganisms are gradually changing from the lower to the upper genital tract with decreasing bacterial abundance and increasing bacterial diversity. It is well documented that the endometrium is a non-sterile area, and in healthy women, the Lactobacillus spp. is the dominant flora. Lactobacillus - as a dominant endometrial microbiome, has a crucial role in implantation, early pregnancy development. It is also essential for a good pregnancy outcome. Non-Lactobacillus-dominant microbiome is associated with poor reproductive outcomes (recurrent implantation failure, recurrent miscarriages, outgoing pregnancy). This association is evidence of its significance for reproductive health. We present a case of unsuccessful first pregnancy with concurrent bacterial endometrial infection. A definitive antibiotic treatment resulted in a successful full-term second pregnancy. We present the influence of pathogenic microorganisms on uterine function and pregnancy development, current possibilities for diagnosis and treatment.